To detect, to deter, to defend: the Distant Early Warning (DEW) line and early cold war defense policy, 1953-1957 - Isemann, James Louis (Kansas State University, 2009)
The Distant Early Warning (DEW) Line, a key program under President Dwight D. Eisenhower’s “New Look” policy, prepared the United States defense posture for “the long haul” in the Cold War. Eisenhower wanted to prevent the escalation of military costs while still providing an adequate defense. Eisenhower emphasized a retaliatory capability and improved continental defenses, the so-called “sword and shield,” which are key features of the New Look. The DEW Line would prove to be a vital component of both. Whereas the initial emphasis of the DEW Line was to warn against attack providing for both active and passive defense measures, soon there was a definite “counter-offensive” role for the DEW Line as well—the protection of the primary retaliatory capability of the United States: the Strategic Air Command (SAC). The place of the DEW Line in the history of the Cold War has been an under appreciated topic. With the exception of the scholarship from the 1950s and early 1960s, only recently have continental defense and particularly the DEW Line been removed from the shadows of other Cold War events, strategies, and military programs. This doctoral thesis is an account of the DEW Line’s conception, implementation, and position in Eisenhower’s New Look and deterrent strategy. The DEW Line proved to be a cardinal feature of Eisenhower’s New Look strategy: it strengthened overall U.S. defenses and defense posture as the one element of U.S. defense policy (“New Look”) that improved and connected both the active and passive measures of continental defense by providing early warning against manned bombers flying over the polar region; it bolstered the deterrent value of SAC; and it was instrumental in developing closer peacetime military cooperation between the United States and Canada. In fact, U.S.- Canadian diplomacy during the 1950s offers an important case study in “superpowermiddle power” interaction. However, despite the asymmetry in their relationship, U.S.- Canadian defense policies proved to be analogous. All of these objectives could not have been accomplished without the technological and logistical abilities necessary to construct successfully the DEW Line.
Keywords: United States History; Continental defense; Cold War; Distant Early Warning Line; DEW Line; National defense; History, United States (0337)